FRI0111 Dental Association or Incidental Finding? A Meta-Analysis and Systematic Review of The Relationship between Rheumatoid Arthritis and Periodontitis. (15th July 2016) - Fuggle, N.R.; Smith, T.O.; Kaul, A.; Sofat, N.
Abstract : Background: Rheumatoid arthritis (RA) and periodontitis are both chronic inflammatory diseases sharing potential mechanisms including histopathology and demography. An association between these conditions has been demonstrated previously but published studies have not been subjected to meta-analysis with respect to large populations worldwide to fully unravel associations across distinct ethnicities. Objectives: The aim of this analysis was to interogate the relationship between rheumatoid arthritis and periodontitis in the context of the earliest to the most recent literature. Methods: The published databases MEDLINE, EMBASE and PsycINFO were searched using search terms related to RA and periodontitis. Articles were selected if they included data on the number of people with RA diagnosed with periodontitis (or periodontal disease parameters) compared to a control comparison group. Review articles, case reports, animal model studies, non-English language and articles with unavailable abstracts were excluded. Data was extracted, critically appraised using the Downs and Black appraisal tool and a fixed-effect Mantel-Haenszel meta-analysis was performed. Results: A total of 21 papers met the eligibility criteria and provided data for the meta-analysis; 17 studies (including a total of 153, 492 participants) comparing RA to healthy controls and 4 (including a total of 1378 participants) comparing RA to osteoarthritis (OA) were evaluated. Studies included patients populations from diverse geographical locations including Taiwan, Japan, India, Holland and the United States. There was a significantly increased risk of periodontitis in people with RA compared to healthy controls (RR: 1.13; 95% CI: 1.04, 1.23; p=0.006; N: 153, 277) with a significantly raised mean probing depth, risk of bleeding on probing (BOP) and absolute value of clinical attachment loss in those with rheumatoid arthritis (Figure 1 ). When comparing RA and OA, there was no significant difference in the prevalence of periodontitis, however the risk of BOP was greater in OA than RA. Conclusions: The very strong association between RA and periodontitis is supported by the results of our systematic review and meta-analysis of studies comparing RA to healthy controls Our data show that the association of RA and periodontitis is a significant observation seen worldwide across a range of ethnicities, suggesting common shared mechanisms in both conditions. Future work is required to unravel the basic molecular pathways underlying RA and periodontitis. Disclosure of Interest: None declared